KREATIVITAS KEPALA SEKOLAH DALAM PEMASARAN PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA NEGERI 34 MUARO JAMBI - Wardani, Miki; Susanti, Try; Savitri, Riftiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the creativity of the principal in marketing educational services at SMP Negeri 34 Muaro Jambi, to identify supporting and inhibiting factors, and to analyze the efforts undertaken in implementing creative educational marketing strategies. This research was motivated by the increasingly competitive educational environment and the fluctuating number of student enrollments despite the existence of various school programs. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, and school staff as research participants. The data were analyzed using data reduction, data display, and conclusion drawing. The results of the study indicate that the principal’s creativity in educational marketing is reflected in the development of flagship programs, the utilization of digital media and social networks, the strengthening of school branding, and the establishment of cooperation with parents and the surrounding community. Supporting factors include the commitment of school stakeholders, adequate facilities, and positive community responses, while inhibiting factors consist of limited human resources, time constraints, and diverse socio-economic backgrounds of the community. The principal’s efforts focus on strengthening communication strategies, optimizing school programs, and enhancing collaboration among school members. These findings show that the creativity of the principal plays an important role in strengthening the school’s image and increasing public interest in enrolling students at SMP Negeri 34 Muaro Jambi.